AB0747 The effect of certolizumab pegol on radiographic progression over 4 years of treatment in patients with psoriatic arthritis. (15th June 2017) - Heijde, D van der; Fleischmann, R; Wollenhaupt, J; Deodhar, A; Bauer, L; Hoepken, B; Peterson, L; Mease, PJ
Abstract : Background: The RAPID-PsA trial (NCT01087788 ) investigated the efficacy and safety of certolizumab pegol (CZP) in patients (pts) with psoriatic arthritis (PsA). It demonstrated that CZP treatment inhibits radiographic progression over 96 weeks (wks). 1 Objectives: We report the long-term effect of CZP treatment on radiographic progression in pts with PsA over 4 years. Methods: The RAPID-PsA phase 3 trial was double-blind and placebo-controlled to Wk24, dose-blind to Wk48, and open-label (OL) to Wk216. Pts had active PsA and had failed ≥1 DMARD. Pts randomized to CZP (200mg Q2W or 400mg Q4W, following 400mg loading dose at Wks0, 2, 4) continued their assigned dose in the OL period. Radiographs taken at baseline (BL), and at Wks96, 168, 216, were read in a single reading campaign using the modified Total Sharp Score (mTSS) for PsA by 2 readers, blinded to patient information and time point sequence. The mean of the scores of the 2 readers was used. Outcomes reported are the least squares (LS) mean mTSS score, change from BL (CFB) in mTSS score, and the percentage of pts assessed for radiographic damage who achieved mTSS non-progression (defined either as CFB in mTSS score ≤0.5 or ≤0), for all Wk0 CZP-treated pts, irrespective of dose regimen. mTSS score and CFB were estimated using Mixed Model Repeated Measures (MMRM) estimates; proportions of pts with radiographic non-progression are presented as observed case. Results: 409 PsA pts were randomized, of whom 273 received CZP from Wk0. The LS mean BL mTSS score was 16.0 and there was little increase from BL in mTSS score to Wk216 (Table). Amongst those who completed the study to Wk216, the majority of CZP-treated pts achieved radiographic non-progression to Wk216, both with non-progression defined as CFB in mTSS score ≤0.5 or ≤0 (Table). The change in LS mean mTSS score over time for Wk0 CZP-treated pts was consistently low throughout the trial: 0.14 (95% CI: 0.02–0.26) per 48 wks from BL to Wk96, and 0.18 (95% CI: 0.08–0.28) per 48 wks from Wk96 to Wk216. Conclusions: There was little radiographic progression in CZP-treated PsA pts, as measured by mTSS, throughout the 4-year RAPID-PsA trial. References: Mease P. RMD Open 2015;1:e000119;doi:10.1136/rmdopen-2015–000119. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Daiichi, Eli Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, UCB Pharma, Employee of: Director of Imaging Rheumatology B.V., R. Fleischmann Grant/research support from: Genentech Inc, Roche, Abbott, Amgen, UCB Pharma, Pfizer, Bristol-Myers Squibb, Eli Lilly, Sanofi-Aventis, MSD Pharmaceuticals, Novartis, AstraZeneca, Janssen, Consultant for: Roche, Abbott, Amgen, UCB Pharma, Pfizer, Bristol-Myers Squibb, Eli Lilly, Sanofi-Aventis, Novartis, AstraZeneca, Janssen, J. Wollenhaupt Grant/research support from: UCB Pharma, Consultant for: UCB Pharma, A. Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GlaxoSmithKline, Janssen, Novartis, Pfizer, UCB Pharma, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer, UCB Pharma, L. Bauer Employee of: UCB Pharma, B. Hoepken Employee of: UCB Pharma, L. Peterson Employee of: UCB Pharma, P. Mease Grant/research support from: (Abbott) AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer, Sun, UCB Pharma, Consultant for: (Abbott) AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, Corrona, Dermira, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Sun, UCB Pharma, Zynerba, Speakers bureau: (Abbott) AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Crescendo, Genentech Inc, Janssen, Novartis, Pfizer, UCB Pharma